Estimating Potential for Drug Budget Reallocation Following Expiration of Exclusivity of Pharmaceutical Products - Samira Toghanian; John Moshtaghi-Svensson; Maria Papageorgiou; Kristin Kittelsen; Christiaan Dolk; Markus Hultstrand; Stina Salomonsson (Journal of Health Economics and Outcomes Research)
# Background The prioritization of public funds in an equitable and ethically sound manner along with efficient budget allocation are key challenges for governments and budget holders. Following the introduction of generics/biosimilars, the potential total budget made available for reallocation resulting from the loss of exclusivity (LOE) in a given market has not been estimated.